Fish Swim Bladder‐Derived ECM Hydrogels Effectively Treat Myocardial Ischemic Injury through Immunomodulation and Angiogenesis - Yulong Fu; Canran Gao; Hailing Zhang; Jing Liu; Boxuan Li; Wei Chen; Xiuping Chen; Xue Lin; Ligang Fang; Zhihong Wang (Advanced Science)
Abstract Injectable hydrogel implants represent a promising therapeutic approach for ischemic heart failure; but their efficacy is often limited by low bioactivity, poor durability, and inadequate injection techniques. Herein, a unique hydrogel incorporating extracellular matrix from fish swim bladder (FSB‐ECM), which has distinct advantages over mammalian derived ECM, such as low antigenicity, bioactivity, and source safety, is developed. It consists of collagen, glycoproteins, and proteoglycans, including 13 proteins common in the myocardial matrix and three specific proteins: HSPG, Col12a1, and vWF. This hydrogel enhances cardiac cell adhesion and stretching while promoting angiogenesis and M2 macrophage polarization. In addition, its storage modulus (G′) increases over time, reaching about 1000 Pa after 5 min, which facilitates transcatheter delivery and in situ gelling. Furthermore, this hydrogel provides sustained support for cardiac contractions, exhibiting superior longevity. In a rat model of ischemic heart failure, the ejection fraction significantly improves with FSB‐ECM treatment, accompanied by increased angiogenesis, reduced inflammation, and decreased infarct size. Finally, RNA sequencing combined with in vitro assays identifies ANGPTL4 as a key protein involved in mediating the effects of FSB‐ECM treatment. Overall, this new injectable hydrogel based on FSB‐ECM is suitable for transcatheter delivery and possesses remarkable reparative capabilities for treating heart failure.